Using the Genetic Algorithm in Developing a Method for Steganography - Nadia Mohammed (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper has developed a method for hiding in images, as it was first encrypt the secret message chaoticlly using the chaotic encryption algorithm and secondly execute the steganography in two phases, the first divide the cover image (.BMP, .PNG) to a group of sections (Blocks) with the diagonal sequence and make hiding using the cell of the least Significant Bit (LSB) within (Bytes) of certain randomly, and then using the Genetic Algorithm (GA) and working at the expense of Peak Signal to Noise Ratio(PSNR)  for each section after the steganography and then get the best PSNR value of the optimal section (ie, a better distribution of the random sites). The second include a final for all sections (Blocks) depending on the results of the first stage and the best for a random distribution of sites (Bytes) according to the results of genetic algorithm. Measuressuch as PSNR, BER, MSE and NC are used to prove the accuracy of the results and efficiency. The application implemented using Matlab 9.